Anti-TNFα therapy in the management of psoriasis: experience of a state referral center - Laura Maria Andrade Silva; Bruno de Oliveira Rocha; Ana Cláudia Pinto Nobre; Vitória Regina Pedreira de Almeida Rêgo; Ivonise Follador; Maria de Fátima Santos Paim de Oliveira (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND:Psoriasis is a chronic immune-mediated disease, characterized by increased levels of TNFα. Anti-TNFα agents have revolutionized the treatment of severe psoriasis by targeting an important molecule involved in its pathogenesis.OBJECTIVES:We report the experience of a state referral center that uses anti-TNFα agents for psoriasis.METHODS:We conducted a retrospective case series. Seventy-four out of 120 patients met the inclusion criteria. Clinical and laboratory data was analyzed using the chi-squared, Wicoxon and McNemar's tests. Associations were considered statistically significant when p-value<0.05.RESULTS:Forty-one subjects (55.40%) were male, with a mean age of 47.69±14.99 years. Median disease duration and pre-treatment PASI were 14.0 months (IQR 9.0-20.0), and 13.55 points (IQR 8.5-20.32). Sixty patients (81.10%) had arthropathic psoriasis. Forty-six subjects (62.20%) had comorbidities; the most frequent was dyslipidemia (25.70%). In 55.40% of patients, insufficient response to conventional therapies was the principal indication for using anti-TNFα drugs. Clinical improvement occurred in 93.20% of cases, and the post-treatment PASI median was 0.0 points (IQR 0.0-0.0). Adverse effects occurred in 6.80% of patients. Infections and elevation of transaminases occurred in 28.40% and 8.10% of cases, respectively.CONCLUSION:Post-treatment reduction in PASI was satisfactory and the occurrence of adverse effects was minor, mostly mild infusion effects and local reactions at drug administration sites.